The Urgency Littoral States in Melacca Strait to Eradicate The Marine Pollution - Pulung Widhi Hari Hananto (Administrative Law and Governance Journal, 2020)
The Strait of Malacca is one of the strategic and potential straits in the world. On the other hand, this strait can be classified as one of the busiest straits in the world, this is indicated by the existence of 60,000 vessels that pass through this strait each year. This is because the volume of vessels continues to increase every year and this has a significant impact on the marine environment. To overcome this, it is necessary to have harmonization and cooperation between littoral countries in overcoming environmental issues around the Malacca Strait. This situation raises the essentiality and urgency of the littoral state to be pro-active in taking a preventive attitude and overcoming the issue of marine pollution. Keywords: the urgency, littoral states, marine pollution, Malacca Strait.